Educational Reform: An Interview with Commissioner J. Duke Albanese - Albanese, J. (Maine Policy Review, 1997)
Few issues touch the hearts, minds, and lives of Mainers more than education. Learning Results, budgetary concerns, violence in schools, and school choice are among the issues that occupy much of the public policy focus of educators, administrators, taxpayers, and lawmakers alike. In this interview, Commissioner J. Duke Albanese addresses some of these education issues, most notably Learning Results and their potential impact on education in Maine.